PENGGUNAAN MEDIA SOSIAL DALAM BERDAKWAH: STUDY TERHADAP DA’I DI KOTA PADANG - Sulastri, Irta; Gustia, Arifah Yenni; Juniati, Lesnita (Universitas Islam Negeri Imam Bonjol Padang, 2020)
Da'wah through social media can either be read by users anywhere and anytime as long as it is connected to the internet network or be shared by users more widely to other users. The problem in this study was how da'i used social media, what contents were included in social media, and what were the considerations used by him/her in posting contents. This research method was qualitative to obtain data on how da'i used social media in dakwah and to obtain data about the considerations of da’i in posting content on social media. Meanwhile, to obtain data about the content posted by da'i, the content analysis method was used. The subjects of this research were da’i who preach in Padang who actively and regularly used social media in their dakwah. The findings of this study indicated that the way da’i used social media was commonly done independently and some were assisted by their team. Apart from that, da'i posted religious content on their Facebook and some also created a closed Facebook group. Content shared by da'i on social media about tauheed, worships and muamalah in the form of social criticism, tausiah, motivation, invitations, and sayings. Meanwhile, the da'i considerations in posting religious content in order to address issues that develop in society by answering netizens’ questions on social media, and took their own initiative and to provide enlightenment.